Analysis of the Field of Rationality from the Perspective of Thomistic Substantialism - Zhuravskyy, Vladyslav (Studia Warmińskie, 2021)
The author’s purpose is to analyse J. Życiński’s concept of the field of ratio[1]nality from the perspective of Thomistic substantialism, especially the concept of be[1]ing developed by M.A. Krąpiec and his co-workers and followers. The first paragraph presents J. Zyciński’s concept of the field of rationality. Then, in the second para[1]graph, the substantialism standpoint presented by Thomist philosophers from Lublin and St. Thomas Aquinas’ concept of ideas is discussed. In the last paragraph, the fol[1]lowing conclusions are drawn from the analysis of the understanding of the ontic sta[1]tus of the laws of nature within some theories of Thomistic substantialism: (1) the universe of possible physical states does not exist as some general idea in God, but is God’s eternal plan, belonging to God’s essence; (2) the laws of nature do not ex[1]ist in themselves, but are sited in concrete individual things and exist in an individua rather than a general way; (3) the appearance of new laws of nature in the universe can only be due to the emergence of individuals of a new species or genus.